Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. Demographic Variables and Their Impact on Job Satisfaction Levels Among Employees of Government Units in OmanMs. Amira Hamed Said Al-Ubaidani,  Dr. Ouazzani Touhami Zineb2. Integration between management and accounting and its role in enhancing the effectiveness of planning and controlLecturer \ Abadelrhem A. B. Alfageeh, Lecturer \ Rayad I. S. Mohamed3. The impact of service quality dimensions on The Jordanian private medical laboratory performanceDr. Mohammed Omar Aldaaeeq,Co-Prof. Al-Harith Mohammed Abu Hussein4. Motivation and its relationship to the performance of workers  from a conceptual perspectiveMs. Turkeah Salah R. Al-Hussaini5. The Impact of Corporate Governance Mechanisms on the Quality of Financial Reporting Information: A Field Study on Some Banks and Companies in the Red Sea and Kasala States, SudanAsst-Prof. Waleed Hussein Hassan Hussein6. Employing the KEDA Model in Evaluating the Performance of Industrial Companies in Palestine and Jordan during 2021 - 2022Dr. Salem Mohammad Salem, Dr. Saeid Abdelkader Zbayneh7. Civil liability arising from the damages of cyberbullying: Towards legal protection for victims in the digital environmentMr. "Mohammad Ali" Jehad Sarah8. The Legal Rule: Between Regulation and ObligationMr. Ayad Kadhim Sadoon, Prof. Akram Hassan Yaghi9. Challenges of Successful Implementation of Artificial Intelligence in Logistics Project Management at Saudi Telecom CompanyDr. Norah Abdullah Al-Subaie
Keywords: Journal of Economic, Administrative and Legal Sciences